PENGARUH INDEKS DOW JONES INDUSTRIAL, NIKKEI 225 DAN FTSE TERHADAP IHSG DAN PENANAM MODAL ASING INDONESIA - Sunarto Sunarto (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
A lot of capital invested is a hope. But as a consequence the state must increase the domestic capital market. This study aims to see how the determination of the international stock market for domestic investment. The research method uses quantitative, simple random sampling techniques, and analysis uses panel regression. The results showed the dominance of DJIA on Indonesian stock prices. This finding confirms that DJIA is an international factor whose work is very sensitive to domestic stocks. Therefore, it is important to establish specific management that addresses the DJIA problem. In addition, the results showed that the CSPI had a positive contribution to foreign investment. Of course this implies, that the JCI is always seen by foreign investors, a matter of lucrative possibilities. Keywords: DJIA, Nikkei 225, FTSE, ICI, Foreign Capital Cultivation